Magnetic behaviour of TbPc(2) single-molecule magnets chemically grafted on silicon surface - Mannini, Matteo (2014)
Single-molecule magnets (SMMs) are among the most promising molecular systems for the development of novel molecular electronics based on the spin transport. Going beyond the investigations focused on physisorbed SMMs, in this work the robust grafting of Terbium(III) bis(phthalocyaninato) complexes to silicon surface from a diluted solution is achieved by rational chemical design yielding the formation of a partially oriented monolayer on the conducting substrate. Here, by exploiting the surface sensitivity of X-ray circular magnetic dichroism we evidence an enhancement of the magnetic bistability of this single-molecule magnet, in contrast to the dramatic reduction of the magnetic hysteresis that characterises monolayer deposits evaporated on noble and ferromagnetic metals. Photoelectron spectroscopy investigations and density functional theory analysis suggest a non-innocent role played by the silicon substrate, evidencing the potentiality of this approach for robust integration of bistable magnetic molecules in electronic devices.